Masseter Muscle Metastasis of Renal Cell Carcinoma: A Case Report and Literature Review - Qin, Fei; Zhang, Xiaofei; Zhang, Jie; Liu, Shuaihong; Wang, Zijie; Xie, Fei; Zhang, Mingxin; Zhang, Tianwei; Wang, Shuangyi; Jiao, Wei (Frontiers in Oncology, 2022)
Background: Patients with renal cell carcinoma are often troubled by metastases, but masseter muscle metastases are particularly rare. Case Presentation: We reported a 76-year-old male who did not show any recurrence and metastasis after the nephrectomy until 5 years later. The metastatic mass was found with the protrusion of masseter muscle area. Computed tomography and ultrasonography indicated a hypervascular mass, and pathology confirmed the masseter muscle metastasis of renal cell carcinoma. Complete metastasectomy was performed with the preserval of facial function and appearance. No local recurrence or distant metastasis was found in follow-up. Conclusion: Our report indicates masseter muscle can be a metastatic site of renal cell carcinoma, regardless of its rarity. Long-term comprehensive surveillance is needed for patients with renal cell carcinoma. Muscle metastases can disguise as benign mass, multiple imaging and pathology are important in identifying their sources. If possible, complete metastasectomy with function retention is recommended for masseter muscle metastases.